Spiritual and Religious Care: Contribution to the Humanization of Assistance (Revista Iberoamericana de Bioética, 2018)
Our times are characterized by individualism from which arises a constant search for meaning, mostly when a person faces death, caused by disease. Therefore, when we consider the relevance of spirituality to an individual’s well-being it somehow has a purpose particularly if we focus on humanization of health care.
Keywords: spirituality; individual; spiritual care; humanization